Efficient Conversion of Epoxides into Carbonates with CO2 and a Single Organocatalyst: Laboratory and Kilogram-Scale Experiments - Azzouz, Rabah; Contreras Moreno, Viviana; Herasme-Grullon, Clara; Levacher, Vincent; Estel, Lionel; Ledoux, Alain; Derrouiche, Salim; Marsais, Francis; Bischoff, Laurent (Synlett, 2020)
Cheap and readily available 2-aminopyridine and related compounds can be used as organocatalysts for the conversion of epoxides into cyclic carbonates. This reaction gives high conversions under solvent-free conditions and is amenable to a kilogram-scale conversion under mild conditions.
Keywords: epoxides; cyclic carbonates; carbon dioxide; organocatalysis; aminopyridine